2017
DOI: 10.3390/urbansci1040032
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Overlap between Cadastral and Visual Boundaries: A Case Study from Vanuatu

Abstract: Cadastres are argued as an essential tool to support land tenure security. Low cadastral coverage in developing countries creates a driver for innovative methods to expedite the mapping processes. As a human construct, the morphology of parcel boundaries is a diverse and complex topic: there are limited generalized rules for identifying, describing, and classifying them. This paper studies both the institutional and spatial aspects of cadastral boundaries, in order to provide more contemporary knowledge about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
28
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 22 publications
1
28
0
Order By: Relevance
“…Automated cadastral boundary delineation based on remote sensing data has been rarely investigated, even though physical objects, which can be extracted using image analysis, often define visible cadastral boundaries [3]. Visible cadastral boundaries demarcated by physical objects such as hedges, fences, walls, bushes, roads, or rivers, can make up a large portion of all cadastral boundaries [4,5]. Indirect surveying relies on the delineation of such visible parcel boundaries from remote sensing imagery.…”
Section: Introductionmentioning
confidence: 99%
“…Automated cadastral boundary delineation based on remote sensing data has been rarely investigated, even though physical objects, which can be extracted using image analysis, often define visible cadastral boundaries [3]. Visible cadastral boundaries demarcated by physical objects such as hedges, fences, walls, bushes, roads, or rivers, can make up a large portion of all cadastral boundaries [4,5]. Indirect surveying relies on the delineation of such visible parcel boundaries from remote sensing imagery.…”
Section: Introductionmentioning
confidence: 99%
“…In developed countries, the extracted visible boundaries might be used for the revision of existing cadastral maps. However, in both cases, the extracted visible boundaries must be validated by landowners and other beneficiaries.(continuous recording of person-right-land relation attributes, in any land related event, as close as possible to real-time) also requires a flexible and dynamic cadastral system [2,7]. Proposed cadastral surveying techniques are mostly indirect ones rather than ground-based.…”
mentioning
confidence: 99%
“…The term updating can be used as a synonym for a "revision" of existing cadastral maps [23]. However, in all case studies reported in [22], cadastral boundaries are manually delineated.It is argued that a large number of cadastral boundaries are visible and coincide with natural or manmade physical object boundaries [2,24,25]. In the land administration domain, automatic extractions of visible cadastral boundaries have been a recent topic of investigation.…”
mentioning
confidence: 99%
See 2 more Smart Citations